IMPLIKASI HUKUM INTERNASIONAL DENGAN HUBUNGAN ANTAR NEGARA - I Kadek Calvin Andreantika (Jurnal Ilmu Hukum Sui Generis, 2022)
The law of nations, sometimes known as international law or the law between states, is essentially the same thing as international law. In the past, the law of nations was utilized to illustrate the norms of behavior and legal guidelines that applied to the relationships that existed amongst ancient rulers. The intricate interplay of laws and principles that govern the relationships between individuals who are members of the same community of nations or states is reflected in either the law of the country or international law. To meet the needs of life and the existence of the existence of a state in the governance of international relations, cooperative relations between countries (international) in the world are required. This is in addition to the creation of peace and well-being, which is a dream for every man and nation in the world. Cooperative relations between countries (international) in the world are required. Naturally, every nation has both positive and negative aspects to its situation, as well as varying priorities and interests. These are the kinds of things that are conducive to fostering relationships and international collaboration. The method of research that was used in the writing of this journal was to use the method literature from a variety of references. a. These references can support the content of the writing, and the final section is where the authors come to a conclusion about what they found.